Elevated Endostatin Expression Is Regulated by the pIgA Immune Complex and Associated with Disease Severity of IgA Nephropathy - Yaling Zhai; Xiaoqing Long; Jingge Gao; Xingchen Yao; Xinnian Wang; Zhanzheng Zhao (Karger Publishers, 2020)
Background/Aims: Renal vascular injury accounts for the poor outcomes of patients with IgA nephropathy (IgAN). In this study, we investigated whether endostatin, a potent inhibitor of angiogenesis, is associated with IgAN. Methods: Serum endostatin levels were detected in patients with IgAN, disease controls, and healthy controls, and the correlation among endostatin and clinicopathologic manifestations, as well as prognosis in patients with IgAN, was analyzed. In addition, serum endostatin levels were compared in patients "before" and "after" treatment. Data on endostatin expression in the renal interstitium of patients with IgAN were downloaded and analyzed from the GSE35489 array in the GEO database. The poly-IgA1 (pIgA) immune complex is widely recognized as the "trigger" of IgAN initiation. pIgA in the plasma of patients was extracted and used to stimulate human glomerular endothelial cells (GECs). Endostatin, IL-6, and CXCL1 in the cell supernatant were detected by ELISA kits. Results: We found that serum endostatin levels were significantly increased in patients with IgAN, as was endostatin expression in the renal interstitium. Patients with IgAN were divided into 2 groups according to the median value. The high endostatin expression group had significantly higher levels of serum creatinine and BUN and more severe tubular/interstitial damage. Moreover, patients with arteriolar injury and endothelial cell proliferation had higher serum endostatin levels. Patients with high serum endostatin levels had poor prognosis. According to the in vitro experiment, the GEC apoptosis rate and the supernatant levels of endostatin, IL-6, and CXCL1 were significantly increased following pIgA stimulation. Conclusion: Our study found that elevated endostatin expression was associated with disease severity and poor prognosis in patients with IgAN and can be upregulated by pIgA, but how it participates in the pathogenesis of IgAN deserves further exploration.